Effect of pad codewords modification on JAKIM halal logo size - Rohani, Fuaad; Mashohor, Syamsiah; Ramli, Abdul Rahman (Halal Products Research Institute, Universiti Putra Malaysia, 2014)
In recent years, JAKIM has utilized halal logo verification using QR codes at food premises and the QR code carries information such as premise name, address, reference number, halal certificate expiry date, generated number and serial number. A small JAKIM halal logo is placed on the top right of the QR code covering the finder pattern and caused the failure of the QR code to be decoded by some decoders. Many works have been conducted to put images on QR code without sacrificing decoding efficiency and pad codewords is one of the effective methods that manipulates unimportant data module to reduce errors. This paper investigates the size of JAKIM Halal logo that can be inserted on top of QR code that contains important information for offline halal logo verification by manipulating the pad codewords. The QR code module size is set to 1 pixel and error correction level is set to M. A QR code will be generated iteratively for certain combinations of QR code version and various selection of location of pad codewords. Later, the unbinarized JAKIM Halal logo will be placed on the selected location of pad codewords in the QR code. The logo size will be increased until it filled the selected QR code area. As the QR code version increased, the pad codewords count will be increased and consequently the overlapped image size can be increased without decoding error. From the experiment, logo size of 41 pixels square (42% logo over QR code ratio and decodable location ratio of about 0.58%) can be overlapped as the QR code version increased from 15 to 20. For 30 pixels logo size (35% ratio), the decodable location can achieve more than 95%. In conclusion, we observed that increasing the QR code version could increase the overlapped logo size, but maintain the decoding performance, which can be read by other decoders that failed to read existing QR code with JAKIM Halal logo.